Development of an electronic module on the subject of ecosystems and environmental changes based on problem-based learning assisted by augmented reality macrozoobenthos - Alvionita, Devi; Ibrohim, Ibrohim; Sueb, Sueb; Memiasih, Novela; Hardyanto, Yanang Surya Putra (AIP conference proceedings, 2024)
The impact of changes in technology, information, and communication (ICT) is currently playing a tremendous role in the education system. Changes in student learning patterns, which are influenced by technology, are one of the big challenges that need to be addressed immediately. Related to this problem, development research was carried out that aims to develop technology-based teaching materials that meet valid and practical requirements. This research consists of five stages, which refer to the model of Lee and Owen (2014); these are assessment and analysis, design, development, implementation, and evaluation. Quantitative data were analyzed descriptive quantitatively from the results of validation, trials, and practical results of teaching material. Qualitative data were analyzed descriptive qualitative obtained from suggestions and comments from validators, biology education practitioners, and students. The trial and implementation of teaching material were carried out at MAN 1 Jember from May to June 2022. The results showed that teaching materials validity reached 100% from material experts and media experts in the very valid category, reaching 93% of biology education practitioners in the very valid category and 97% of the trials in the very valid category. The results of the practicality test reached 88.1% in the very practical category. From this research, it can be concluded that the electronic module for ecosystems and environmental change learning based on PBL and assisted by augmented reality is valid and practical, which can be used in subsequent research.